Pengaruh Implementasi Kebijakan Online Single Submission, Kompetensi Pegawai Dan Pelatihan Terhadap Pelayanan di Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu DKI Jakarta - Mega Fitria Sari; Saifullah (Reformasi Administrasi, 2025)
This research aims to analyze the effect of the implementation of the OSS policy, employee competence, and training on services at the Investment and One-Stop Integrated Service Office (DPMPTSP) of DKI Jakarta. The research method used is quantitative research with a questionnaire as the data collection technique with a sample size of 154 individuals selected through probability sampling. The results show that the implementation of the OSS policy, employee competence, and training individually have a positive and significant effect on service, and collectively, the three independent variables contribute positively and significantly to services at DPMPTSP DKI Jakarta. This is supported by an F value of 64.003, which is greater than the F table value of 2.66, and a significance level of 0.000, which is smaller than the significance probability α = 0.05. The coefficient of determination is 0.561, indicating that the combined effect of the OSS policy implementation, employee competence, and training accounts for 56.1% of the variation in the service variable, while the remaining 43.9% is affected by other variables not included in this research.